INTRAVITREAL INJECTION OF PERFLUOROPROPANE IS MORE EFFICACIOUS THAN SULFUR HEXAFLUORIDE IN RELEASING VITREOMACULAR TRACTION - Čokl, Neža (Acta Clin Croat, 2018)
SUMMARY – The aim was to compare the efficacy of a single intravitreal injection of perfluoropropane (C3F8) and sulfur hexafluoride (SF6) in releasing vitreomacular traction (VMT). This prospective study included two groups of patients with symptomatic VMT confirmed by spectral-domain optical coherence tomography (SD-OCT). Patients from both groups received a single intravitreal injection of expansile gas. One group (29 eyes) received 0.3 mL of 100% C3F8, and the other group (28 eyes) received 0.3 mL of 100% SF6. Eyes without VMT release one month after SF6 injection were secondarily injected with C3F8. The primary outcome was the ratio of eyes in each group with complete VMT release on OCT one month following primary treatment. The secondary outcome was the ratio of reinjected eyes with complete VMT release on OCT one month following second injection. Additional outcome was the ratio of VMT release in eyes with specific clinical characteristics. One month after the application, complete release of VMT on OCT was recorded in 18 out of 29 eyes (62%) in the C3F8 group, in 6 out of 28 eyes (21.4%) in the SF6 group, and in 7 out of 14 (50%) reinjected eyes. There was no statistically significant difference in age, width of vitreomacular attachment (WVMAT), central retinal thickness and presence of additional features between the two groups. In eyes with WVMAT <500 microns, there was no statistically significant difference between the two gases in releasing VMT. In eyes with WVMAT >500 microns, C3F8 was more efficacious (p=0.001). According to the results of our study, intravitreal C3F8 injection seems to be more efficacious in releasing VMT than SF6 in eyes with WVMAT larger than 500 microns.